Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.07.08.499319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased mitochondrial Ca2+ contributes to health decline with age and Duchene muscular dystrophy in C. elegans

Abstract: Sarcopenia is a geriatric syndrome characterized by an age-related decline in skeletal muscle mass and strength. Here, we show that suppression of mitochondrial calcium uniporter (MCU)-mediated Ca2+ influx into mitochondria in the body wall muscles of the nematode Caenorhabditis elegans improved the sarcopenic phenotypes, blunting movement and mitochondrial structural and functional decline with age. We found that normally aged muscle cells exhibited elevated resting mitochondrial Ca2+ levels and increased mit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Worms were age-synchronized from the eggs and allowed to grow to the designated day. The strains used in this study are as follows: wild-type N2, TG2435: vtIs1 [ dat-1p::GFP + rol-6(su1006) ] V, ATU2301: goeIs3 [ myo-3p::SL1::GCamP3.35::SL2::unc54 3’UTR + unc-119(+) ] V, acels1 [ myo-3p::mitochondrial LAR-GECO+myo-2p::RFP ] II, ATU2305: dys-1(eg33) goeIs3 [ Pmyo3::GCaMP3.35::unc-54-3’utr, unc-119(+) ], aceIs1 [ Pmyo3::mitochondrial LAR-GECO + Pmyo2::RFP ] [ 34 ], ATU3301: ccIs4251 [ (pSAK2) myo-3p::GFP::LacZ::NLS + (pSAK4)myo-3p::mitochondrialGFP+dpy-20(+) ] I, acels1 II, ATU3305:: dys-1(eg33) ccIs4251 [ Pmyo3::nucGFP-LacZ + Pmyo-3::mitochondrial GFP ], aceIs1 [ Pmyo-3::mitochondrial LAR-GECO+ Pmyo2::RFP ], SD1347: ccIs4251 [ (pSAK2) myo-3p::GFP::LacZ::NLS+ (pSAK4) myo-3p::mitochondrial GFP + dpy-20(+) ] I and ATU3307: ccIs4251 I, acels1 II, immt-1 (tm1730) X.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Worms were age-synchronized from the eggs and allowed to grow to the designated day. The strains used in this study are as follows: wild-type N2, TG2435: vtIs1 [ dat-1p::GFP + rol-6(su1006) ] V, ATU2301: goeIs3 [ myo-3p::SL1::GCamP3.35::SL2::unc54 3’UTR + unc-119(+) ] V, acels1 [ myo-3p::mitochondrial LAR-GECO+myo-2p::RFP ] II, ATU2305: dys-1(eg33) goeIs3 [ Pmyo3::GCaMP3.35::unc-54-3’utr, unc-119(+) ], aceIs1 [ Pmyo3::mitochondrial LAR-GECO + Pmyo2::RFP ] [ 34 ], ATU3301: ccIs4251 [ (pSAK2) myo-3p::GFP::LacZ::NLS + (pSAK4)myo-3p::mitochondrialGFP+dpy-20(+) ] I, acels1 II, ATU3305:: dys-1(eg33) ccIs4251 [ Pmyo3::nucGFP-LacZ + Pmyo-3::mitochondrial GFP ], aceIs1 [ Pmyo-3::mitochondrial LAR-GECO+ Pmyo2::RFP ], SD1347: ccIs4251 [ (pSAK2) myo-3p::GFP::LacZ::NLS+ (pSAK4) myo-3p::mitochondrial GFP + dpy-20(+) ] I and ATU3307: ccIs4251 I, acels1 II, immt-1 (tm1730) X.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial Ca 2+ and cytoplasmic Ca 2+ in BWM cells were, respectively, observed by measuring the expression of the transgenes aceIs1 and goeIs3 as described recently from our group [ 34 ]. The Ca 2+ concentration in muscle mitochondria ([Ca 2+ ] mito ) was calculated using the following equation [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ is essential for optimal mitochondrial function, but its overload impairs mitochondrial function, leading to decreased mitochondrial inner membrane potential (ΔΨm) and ATP production, increased ROS release, and ultimately cell death 17 . Our recent ndings indicate that both genetic (mcu-1 mutation) or pharmacological (Ru360 administration) suppression of MCU can ameliorate muscle weakness induced by C. elegans aging and dys-1 (eg33) mutation of DMD model 12 . On the other hand, MA-5 administration reduced mitochondrial Ca 2+ overload induced by aging and rotenone treatment (Fig.…”
Section: Introductionmentioning
confidence: 91%
“…1B,C,D). In addition, we recently found that the BMC's mitochondrial Ca 2+ ([Ca 2+ ] mito ) levels increases with age by using aceIs1 transgene of mitochondrial Ca 2+ sensor mtLAR-GECO 12 . The age-related increase in [Ca 2+ ] mito levels could be suppressed by the administration of MA-5 (Fig.…”
Section: Introductionmentioning
confidence: 99%